2015
DOI: 10.2217/epi.15.7
|View full text |Cite
|
Sign up to set email alerts
|

DNA Methylation as a Diagnostic and Therapeutic Target in the Battle Against Type 2 Diabetes

Abstract: Type 2 diabetes (T2D) develops due to insulin resistance and impaired insulin secretion, predominantly in genetically predisposed subjects exposed to nongenetic risk factors like obesity, physical inactivity and ageing. Emerging data suggest that epigenetics also play a key role in the pathogenesis of T2D. Genome-wide studies have identified altered DNA methylation patterns in pancreatic islets, skeletal muscle and adipose tissue from subjects with T2D compared with nondiabetic controls. Environmental factors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(69 citation statements)
references
References 69 publications
2
65
1
1
Order By: Relevance
“…16 The mean magnitude of the absolute differences in beta values was small, in line with that observed in previous studies of adipose tissue. 16,[29][30][31] Although previous studies have reported global hypomethylation associated with T2D, 24 in the present study no differences were observed in the global methylation levels between IR and IS morbidly obese patients. However, the differential methylation analysis between IR and IS patients revealed genes involved in pathways associated with the function of adipose tissue, such as cell adhesion, signal transduction, and regulation of transcription.…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…16 The mean magnitude of the absolute differences in beta values was small, in line with that observed in previous studies of adipose tissue. 16,[29][30][31] Although previous studies have reported global hypomethylation associated with T2D, 24 in the present study no differences were observed in the global methylation levels between IR and IS morbidly obese patients. However, the differential methylation analysis between IR and IS patients revealed genes involved in pathways associated with the function of adipose tissue, such as cell adhesion, signal transduction, and regulation of transcription.…”
Section: Discussioncontrasting
confidence: 83%
“…Previous studies have highlighted the importance of epigenetic regulation as a mechanism in the pathogenesis of T2D. 24 Detailed information concerning the DNA methylome in human pancreatic islets from T2D and nondiabetic patients has been provided. 14,25 Genome-wide DNA methylation studies in human skeletal muscle from individuals with or without a family history of T2D have also indicated differential methylation in genes involved in insulin signaling and muscle function.…”
Section: Discussionmentioning
confidence: 99%
“…Brain and other tissues also show linear increases of DNA methylation (7). Moreover, during treatment of type 2 diabetes, skeletal muscle DNA methylation responded to exercise and to blood glucose variations (8). Intriguingly, the methylation of genes implicated in diabetes also showed correlations with glycated hemoglobin (HbA1c), a short-term marker for blood glucose exposure.…”
Section: Molecular Aging Morbidity and Mortalitymentioning
confidence: 99%
“…DNA hyper-methylation can silence genes that are profoundly involved in the secretion of insulin and glucagon [229]. Patients with type 2 diabetes express altered GDM in skeletal muscles, adipose tissue, and pancreatic islets [230]. DNA methylation of one CpG site at the promotor glocagone-like-peptide-1 (GLP1R) receptor gene decreases the transcription levels of GLP1R and correlated positively with the body mass index [231].…”
Section: Circadian Disruption Biomarkers In Obesity and Cancer Researchmentioning
confidence: 99%